Perbandingan Metode Double Exponential Smoothing, Moving Average, dan Linear Regression pada Peramalan Permintaan Produk Pipa Spec Non-Api Tipe SNI 0068:2013 Kelas 2 /PKB (STK)-400 di WTM-8 PT XYZ - Supriyatna, Muhamad; Momon, Ade (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
PT XYZ, as one of the leading steel pipe manufacturers in Indonesia, aims to compare the effectiveness of forecasting methods in predicting demand for SPEC NON-API TYPE SNI 0068:2013 CLASS 2 /PKB (STK)-400 in WTM-8. The methods compared include Double Exponential Smoothing, Moving Average, and Linear Regression. The forecasting results show that Linear Regression provides the best accuracy with an MSE of 2,619,446 and a MAPE of 96.80%, compared to Double Exponential Smoothing (MSE: 17,123,634.831, MAPE: 113.65%) and two variants of Moving Average, namely MA (2) (MSE: 4,193,150, MAPE: 136.68%) and MA (2x3) (MSE: 4,273,548, MAPE: 169.84%). These findings emphasize the importance of using Linear Regression for demand forecasting to improve the accuracy and efficiency of production planning. Continuous evaluation of forecasting methods and development of related staff skills are expected to support more effective decision making and reduce operational risks.